The Use of Hot Potatoes in Nahwu Learning - Tunnisa, Ridha; Marsiah, Marsiah; Rahmah, Yulia (Institut Agama ISlam Negeri Palangka Raya, 2022)
The purpose of this study is to know the effectiveness of the use of hot potatoes in nahwu (mubtada khobar) of the class viii MTS Darul Ulum Palangka Raya. In this study using quantitative research methods the true design of experiments that use pre-test and post-test. Based on the research that's been done that 1. The control class student's learning indicates an increase in learning without the use of hot potatoes by the pre-test average of 35.00 and a post-test of 46.36 which is an improvement in post-test results. It was then decided that learning the control class could improve even if it did not use hot potatoes. 2. The study of the experimental student class indicates an increased in the nahwu learning by using hot potatoes was seen by the pre-test average of 48.16 and a post-test of 67.37, which is an increase in post-test results. It was then decided that learning in experimental classes could improve by using hot potatoes. 3. Comparative results of an average post-test experiment and control class using an independent sample t test because of normal distributed data, and gained a value of 0.001 less than 0.05, so there is a significant difference between the two. The information can be concluded that hot potatoes are effective in learning.